Influence Analysisloan Information on Interest Rate in Peer to Peer Lending - Evi Maria; P. Basuki Hadiprajitno (Journal of Business, Social and Technology, 2024)
Technology has developed rapidly and affected every community's life. This condition was also supported by the occurrence of a pandemic in early 2020 which resulted in restrictions on mobility between individuals and other humans to reduce the spread of the virus which resulted in a crisis. One of the technological developments in the financial sector is loan products through the Peer to Peer platform. Namely transactions that use an online platform that functions as an intermediary that connects borrowers and lenders to carry out lending and borrowing transactions without meeting physically. P2P transaction mechanisms that are carried out directly between borrowers and investors provide risk directly to investors for the success of their funding through the P2P platform. Therefore, in conducting a direct analysis of the loans to be financed, investors must have adequate information so that they can make the best analysis for the financing they are doing. This mechanism allows for information asymmetry on the part of borrowers and investors. The level of trust from lenders is an important factor that will influence their decision as investors to provide funds to borrowers. This confidence can be obtained, among other things, by studying the various available information. In addition, there is the phenomenon of an increase in borrowers and lenders in P2P transactions in Indonesia. It is necessary to pay attention to whether this decision affects interest rates for lending through P2P platforms.